\(F=1+\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+....+\frac{1}{2^{2022}}\)
GIÚP VS MỌI NGƯỜI ƠI
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
nè mình gợi ý cho gọi a= 1-1/2-1/2^2-1/2^3-......... ......1/2^2014 1 / 2^2>1 / 2.3 1/2^3>1/3.4 ................ 1/2^2014<1/2014.2015 nen 1-1/2-1/2^2-1/2^3-.........................1/^2014>1-1/1.2-1/2.3-1/3.4-........................1/2014.2015 a<1-[1-1/2015] a<1-2014/2015 a<1/2015
Cách 1 :
\(A=\left(6-\frac{2}{3}+\frac{1}{2}\right)-\left(5+\frac{5}{3}-\frac{3}{2}\right)-\left(3-\frac{7}{3}+\frac{5}{2}\right)\)
\(\Rightarrow A=6-\frac{2}{3}+\frac{1}{2}-5-\frac{5}{3}+\frac{3}{2}-3+\frac{7}{3}-\frac{5}{2}\)
\(\Rightarrow A=\left(6-5-3\right)+\left(\frac{7}{3}-\frac{2}{3}-\frac{5}{3}\right)+\left(\frac{1}{2}+\frac{3}{2}-\frac{5}{2}\right)\)
\(\Rightarrow A=-2+0+-\frac{1}{2}\)
\(\Rightarrow A=-2+\frac{-1}{2}\)
\(\Rightarrow A=-\frac{5}{2}\)
Cách 2 :
\(=\left(\frac{36}{6}-\frac{4}{6}+\frac{3}{6}\right)-\left(\frac{30}{6}+\frac{10}{6}-\frac{9}{6}\right)-\left(\frac{18}{6}-\frac{14}{6}+\frac{15}{6}\right)\)
\(=\frac{35}{6}-\frac{31}{6}-\frac{19}{6}\)
\(=-\frac{15}{6}\)
\(=-\frac{5}{2}\)
~
Ta có: A = \(\frac{1}{1^2}+\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+...+\frac{1}{50^2}<\frac{1}{1^2}+\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{49.50}\)
\(\Rightarrow\) A < \(1+\left(\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{49}-\frac{1}{50}\right)\)
\(\Rightarrow\) A < \(1+\left(1-\frac{1}{50}\right)\)
\(\Rightarrow\) A < 1 + 49/50
Mà 1+49/50 < 2 nên A < 1+49/50 < 2
\(\Rightarrow\) A < 2
\(A=\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{100}}\)
\(2A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{99}}\)
\(2A-A=\left(1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{99}}\right)-\left(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{100}}\right)\)
\(A=1-\frac{1}{2^{100}}\)
\(A=\frac{2^{100}-1}{2^{100}}\)
\(A=\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{100}}\)
\(2A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{99}}\)
\(2A-A=\left(1+\frac{1}{2}+...+\frac{1}{2^{99}}\right)-\left(\frac{1}{2}+\frac{1}{2^2}+..+\frac{1}{2^{100}}\right)\)
\(A=1-\frac{1}{2^{100}}\)
hok tốt!!
Ta có \(F=2F-F=2\left(1+\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{2022}}\right)-\left(1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2022}}\right)\)
\(=2+1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2021}}-1-\frac{1}{2}-\frac{1}{2^2}-..-\frac{1}{2^{2022}}\)
\(=2-\frac{1}{2^{2022}}\)